Improved prediction of critical-viscosity temperature by fusion behavior of coal ash. (1st October 2019) - Yan, Tinggui; Bai, Jin; Kong, Lingxue; Li, Huaizhu; Wang, Zhigang; Bai, Zongqing; Zhao, Huiling; Li, Wen
Highlights: The viscosity above Tcv of glassy slags is higher and the solid formation rate is lower than that of crystalline slags. The large temperature range from DT to FT and the slow fusion rate above FT is the common feature of glassy slags. Predicting Tcv by applying one method to all the crystalline slags and glassy slags is not appropriate. Abstract: Coal ash slag viscosity is critical for slag tapping in entrained-flow coal gasifiers, so the accurate prediction of slag viscosity and the critical temperature of viscosity (Tcv ) will help the coal selection, flux addition and gasifier operation. Many empirical correlation models based on ash fusion temperature have been proposed to calculate Tcv . In order to correlate the viscosity with the fusion behavior and then improve the prediction of Tcv, we measured the viscosity of several synthetic coal ash slags with a high-temperature rotary viscometer and studied their ash fusion behavior through thermomechanical analysis. X-ray diffraction was used to compare the mineral transformation before and after Tcv combined with the FactSage calculation. The viscosity measurement shows that the viscosity above Tcv of glassy slags is higher than that of the crystalline type. The mineral transformation from FactSage also demonstrates that the precipitation rate of solid phase is lower for glassy slags. The fusion behavior for the glassy and the crystalline slag is also distinctly different. The fusion range from deformation temperature (DT) to flow temperature (FT) of the ash for the glassy slag was larger than that of the crystalline one, and the shrinkage above FT in TMA trace slopes gently. The correlation between the fusion behavior and viscosity-temperature behavior for the glassy slag is reasonable, because the large temperature range from DT to FT and the low shrinking rate of the stage III indicate the high viscosity of the liquid phase formed and the slow melting of the remained solid phase respectively, which are also the correlative condition prefer for the formation of glass as mentioned above. For the crystalline slag, the small fusion range from DT to FT means the rapid melting of the solid phase and the high flowability of the liquid phase which are indicative for the rapid precipitation during cooling. The slow rate of the stage III indicates the slow melting of the remained solid which can be the crystal nucleus. When the viscosity of the liquid phase is low, it also benefit for the formation of crystalline slags. The characteristic in fusion behavior for different type of slag also suggested that the predicting Tcv by applying one method to all the crystalline slags and non-crystalline slags is not appropriate.